Alcohol use in a military population deployed in combat areas: a cross sectional study - Hanwella Raveen; de Silva Varuni; Jayasekera Nicholas E L W (BMC, 2012)
Abstract Background Alcohol misuse is more prevalent among military populations. Association between PTSD and heavy drinking have been reported in many studies. Most of the studies on alcohol use among military personnel are from US and UK. Aim of this study is to describe alcohol consumption patterns among military personnel in Sri Lanka, a country where the alcohol consumption among the general population are very different to that in US and UK. Methods Cross sectional study consisting of representative samples of Sri Lanka Navy Special Forces and regular forces deployed in combat areas continuously during a one year period was carried out. Data was collected using a self report questionnaire. Alcohol Use Disorder Identification Test (AUDIT) was used to assess alcohol consumption. Results Sample consisted of 259 Special Forces and 412 regular navy personnel. The median AUDIT score was 2.0 (interquartile range 6.0). Prevalence of current drinking was 71.2 %. Of the current users 54.81 % were infrequent users (frequency ≤ once a month) while 37.87 % of users consumed 2-4 times a month. Prevalence of hazardous drinking (AUDIT ≥ 8) was 16.69 % and binge drinking 14.01 %. Five (0.75 %) had AUDIT total ≥20. There was no significant difference between Special Forces and regular forces in hazardous drinking or binge drinking. Total AUDIT score ≥16 were associated with difficulty performing work. Conclusions High rates of hazardous drinking and binge drinking described among military personnel in US and UK were not seen among SLN personnel deployed in combat areas. This finding contrasts with previously reported association between combat exposure and hazardous alcohol use among military personnel. Alcohol use among military personnel may be significantly influenced by alcohol consumption patterns among the general population, access to alcohol and attitudes about alcohol use. Similar to findings from other countries, heavy alcohol use was associated with poorer psychological health and functional impairment.